Implementasi Manajemen Kurikulum dalam Mengembangkan Kompetensi Guru Di MTs Negeri 1 Kota Prabumulih - Dewi Parhati; Syarwani Ahmad; Nazaruddin Nazaruddin (Journal Of Administration and Educational Management (ALIGNMENT), 2023)
This study aims to find out and describe the implementation of curriculum management in developing teacher competencies in MTs Negeri 1 Prabumulih City. The research method used is a qualitative descriptive method with data analysis techniques, namely data reduction, data presentation, and drawing conclusions. The research findings are as follows; the concept of curriculum management implementation in MTs negeri 1 Prabumulih city is carried out through the stages of curriculum planning by the curriculum development team, curriculum organizing in the form of delegation of authority from the head of the madrasah to the Deputy head of the madrasah for Curriculum, curriculum implementation and curriculum evaluation which is carried out by examining curriculum documents, implementing class supervision and interviews, The implementation of teacher competency development is carried out through the assignment of teachers to take part in training, workshops, seminars or discussion activities through MGMP either held by the madrasah itself or through other institutions. In conclusion, implementing curriculum management in developing teacher competency at MTs Negeri 1 Prabumulih City has been carried out well, starting with the stages of planning, organizing, implementing, and evaluating. Keywords : Curriculum Implementation, Teacher Competency